Commercial Facilities and Urban Regeneration - Ana-Lucia Ristea; Ioan-Franc Valeriu; Ion Stegăroiu; Gabriel Croitoru (Amfiteatru Economic Journal, 2010)
The paper deals with a model for assessing disparities in the development of commercial facilities. The term “commercial facilities” helps one perceive distribution not only as an economic activity in itself but also as an urban infrastructure and as a component of an urban area that forms a town, area which should be designed in accordance with the new concepts promoted by the European Union: integrated town planning, and urban regeneration. The paper consists of three parts: the first part briefly presents the importance of town development from the perspective of the theory of urban area modelling; the second part deals with the functional integration of commercial facilities into urban regeneration projects; the third part suggests a model for assessing regional disparities in the development of commercial facilities, which – using the “point method” – can be applied so that it meets the requirement of quantifying the equipment levels reached and make space comparisons. This model is based on ten indicators relevant to the studied field, as taken from Statistical Yearbook of Romania. For Romania, it is all the more necessary to define programmes for the territorial development of commercial facilities as, at present, major disparities have been caused by the disequilibrium resulted from the uncontrolled expansion of the great multinational distribution chains, which equally hindered the small independent trade and the network of shops specific to the main/historical centres of towns. The outcome of our research confirms the need that local communities should think and act consistently with the new policy of sustainable development of towns, promoted within the European Union, aimed at observing the basic principles of the territory planning policy: restructuring and strengthening the structurally deficient areas.
Keywords: C31; O21; P41; 330; integrated town planning; urban regeneration; commercial town planning; regional disparities; point method; sustainable development